The Characteristics of Mohs Surgery Performed by Dermatologists Who Learned the Procedure During Residency Training or Through Postgraduate Courses and Observational Preceptorships. Issue 2 (1st April 2016) - Steinman, Howard. K.; Clever, Henry; Dixon, Anthony
Abstract : Little is known about the practice characteristics of Mohs surgery performed by physicians who learned the procedure during their dermatology residency training or through postresidency courses and observational preceptorships. All published reports have investigated Mohs surgeons trained in postresidency fellowships. This report presents the results of a multicenter prospective cohort study evaluating 1834 consecutive Mohs surgery cases performed during the same 6-month period by 9 Mohs surgeons who learned the technique in residency or in postresidency courses and observational preceptorships. One major complication was reported, a hematoma requiring outpatient drainage in an emergency room. There were 54 (2.9%) short-term complications, including 20 (1.1%) infections, 17 (0.9%) wound dehiscences, 9 (0.5%) cases of skin flap necrosis, and 8 (0.4%) hematomas or postoperative bleeding episodes. These complication rates and the data evaluating tumor type, anatomic location, primary vs. recurrent tumor status, tumor size, postoperative wound size, number of Mohs surgery stages, and repair type compare favorably to previously published reports.